FORMULATION OF PROBIOTIC CHOCOLATE USING - Arthrobacter globiformis AND FLAXSEED - Rajalakshmi V.,; Nivedha A.,; Vidya P.,; Pavithra A.,; Abirami M, (The Bioscan, 2024)
Concerns regarding food quality have arisen recently, and research on supplementation to increase food's nutritional worth is extensive. One such significant and often utilized functional food supplement is probiotics. Arthrobacter globiformis is a soil microorganism that can have the ability to act as a probiotic in the human body. A probiotic chocolate is made by combining chocolate, flaxseed powder, and Arthrobacter globiformis. Flaxseed rich in dietary fibre, can help us feel fuller for longer. Chocolate, on the other hand, may have anti-inflammatory, antioxidant, and heart-healthy properties as well as lower bad cholesterol, lower blood pressure, and improve brain function. Current research aims to isolate and characterize probiotic bacteria investigate the acid and bile tolerance capacity and utilize them as nutritional supplements by incorporating with chocolates. Probiotic bacteria were isolated from soil using ABM (Arthrobacter medium) medium. The isolated colonies were identified using standard techniques. The isolated microorganism was identified as Arthrobacter globiformis. The mass production of Arthrobacter globiformis was done and lyophilized for further study. The analytical techniques were performed to evaluate the produced probiotic chocolate and its effectiveness towards gut health.